(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2005)
Quality control forms an integral part of precast production. An efficient quality system is most critical in the mass production of precast components in any project. In this study, the quality control system implemented in a precast factory is discussed. The precast factory is set up for the manufacture of large quantity of tunnel segments under a contract. Processes in the precast manufacture are discussed with respect to the control procedures in the quality inspection plan. The standard tests involved, roles of inspectors and corrective actions on-site are highlighted. Critical issues pertaining to the productivity and quality of precast production are reviewed. These include the quality of staff and maintenance, which could potentially affect the efficiency of the quality system. Some considerations should also be given to improve the workflow and productivity of the plant.